2015
DOI: 10.1073/pnas.1414002112
|View full text |Cite
|
Sign up to set email alerts
|

RING finger protein 121 facilitates the degradation and membrane localization of voltage-gated sodium channels

Abstract: Following their synthesis in the endoplasmic reticulum (ER), voltagegated sodium channels (Na V ) are transported to the membranes of excitable cells, where they often cluster, such as at the axon initial segment of neurons. Although the mechanisms by which Na V channels form and maintain clusters have been extensively examined, the processes that govern their transport and degradation have received less attention. Our entry into the study of these processes began with the isolation of a new allele of the zebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…In agreement with its role in the regulation of cellular processes in C. elegans , a recent study also suggests that RNF121 controls distal tip cell migration and NF‐κB signaling . Consistent with our observation, while the current manuscript was in preparation, Ogino et al reported that RNF121 also regulates maturation of voltage‐gated sodium channel .…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with its role in the regulation of cellular processes in C. elegans , a recent study also suggests that RNF121 controls distal tip cell migration and NF‐κB signaling . Consistent with our observation, while the current manuscript was in preparation, Ogino et al reported that RNF121 also regulates maturation of voltage‐gated sodium channel .…”
Section: Discussionsupporting
confidence: 91%
“…Capped, full-length zebrafish polr2d mRNA was synthesized from pCS2 + zPolr2d plasmids using the mMessage mMachine SP6 Transcription Kit (Thermo Fisher Scientific) as described previously 34 . The mRNA was microinjected into 1-2 cell stage embryos and the embryos were subjected for observation at 48 hpf as described previously 35 .…”
Section: Methodsmentioning
confidence: 99%
“…Tactile-evoked zebrafish movements in the presence of control 1% DMSO or drug were video recorded at 48 hpf using a dissection microscope. Touch responses elicited by tactile stimulation delivered to the tail with forceps were captured with a high-speed CCD camera at 200 frames per second (HAS-220, Ditect) as described previously 31 . Embryos were exposed to 70 µM strychnine, 5 mM picrotoxin, 200 µM nifedipine, 500 µM niflumic acid for 30 min before assay.…”
Section: Methodsmentioning
confidence: 99%